Biliary Tract Disease in Girls and Young Women With Rett Syndrome. Issue 6 (June 2019) - Motil, Kathleen J.; Lane, Jane B.; Barrish, Judy O.; Annese, Fran; Geerts, Suzanne; McNair, Lauren; Skinner, Steven A.; Neul, Jeffrey L.; Glaze, Daniel G.; Percy, Alan K.
ABSTRACT: Objective: We reviewed medical records and conducted a nationwide survey to characterize the clinical features and determine the prevalence of biliary tract disease in girls and women with Rett syndrome (RTT). Methods: Sixty-two individuals with RTT and biliary tract disease were identified from the membership of Rett Syndrome Organization and patient files of the principal investigator. Medical records of 46 individuals were reviewed for presenting features, diagnostic tests, and treatment outcomes of biliary tract disease. We designed a questionnaire that probed the frequency of risk factors and treatment outcomes of biliary tract disease in RTT. The questionnaire was completed by 271 parents whose daughters met the clinical criteria for RTT and/or had MECP2 mutations and participated in the Natural History of Rett Syndrome Study. Results: Presenting symptoms identified by record review included abdominal pain (94%), irritability (88%), weight loss (64%), and vomiting (52%). Biliary dyskinesia, cholecystitis, and cholelithiasis were identified in 90%, 77%, and 70%, respectively, by cholescintigraphy, surgical pathology, and abdominal ultrasound. The prevalence of biliary tract disease was 4.4% (n = 12) in the RTT cohort. Risk factors included older age ( P  < 0.001) and a positive family history ( P  < 0.01). Diagnoses included cholecystitis (n = 5), biliary dyskinesia (n = 6), and cholelithiasis (n = 7). Ten individuals underwent surgery; 7 had resolution of symptoms after surgical intervention. Conclusions: Biliary tract disease is not unique to RTT, but may be under-recognized because of the cognitive impairment of affected individuals. Early diagnostic evaluation and intervention may improve the health and quality of life of individuals affected with RTT and biliary tract disease. Abstract : Supplemental Digital Content is available in the text